Factores que obstaculizan a los gobiernos municipales de la provincia de Chimborazo el impulso de la metodología Building Information Modeling (BIM). - Llongo Orozco, Lida Margarita (2024)
Professor Charles M. Eastman, in 1970, was the first to spread the concept of Building Information Modeling as a synonym of BIM, which is a collaborative work methodology for the creation and management of a construction project by centralizing all the project information in a digital information model created by all its agents. BIM is present in all project stages, from conception to operation and maintenance. The use of BIM in neighboring countries has achieved an improvement in productivity, competitiveness, and transparency in the construction sector, while in Ecuador, the management, planning, and execution of projects in public and private construction is deficient because the Ecuadorian government has not been interested in implementing this BIM methodology since it requires a large investment. The objective of this research was to identify the factors that hinder the Municipal Governments of the Province of Chimborazo to promote the BIM Methodology in the architecture, engineering and construction (AEC) industry. Through the findings, it is clear that the audience's role is crucial in overcoming these factors. The research was conducted through semi-structured interviews to managers of the 10 Municipal Governments of the Province of Chimborazo and surveys were applied to technical and operational or managerial personnel based on the parameter of knowing, wanting and being able. A narrative analysis supported by Atlas ti software and descriptive statistics was carried out, contrasting the information and determining that the factors are: lack of promotion and incentive regulations, as well as scarce training in BIM, technological obsolescence, budgetary limitations, poor inter-institutional coordination and resistance to change on the part of certain staff members.